Circulating visfatin levels in healthy preterm infants are independently associated with high-density lipoprotein cholesterol levels and dietary long-chain polyunsaturated fatty acids. - Tania Siahanidou; Margeli, Alexandra; Kappis, Athanasios; Papassotiriou, Ioannis; Mandyla, Helen (Metabolism, 2011)
{The adipokine visfatin has been proposed to exert insulin-mimicking effects and to play a role in the development of metabolic syndrome. Preterm infants are at risk for the later development of insulin resistance and, possibly, for other components of metabolic syndrome. Dietary long-chain polyunsaturated fatty acids (LCPUFAs) during the perinatal period may reduce the risk of metabolic syndrome. The authors’ objective was to study the circulating concentrations of visfatin in preterm infants and to examine associations of visfatin with anthropometric measurements, metabolic indices, and dietary LCPUFAs. Serum visfatin concentrations were determined by enzyme-linked immunosorbent assay at mean (SD) 33.8 (11.7) days of life in 60 healthy preterm infants (gestational age, 32.7 [1.9] weeks) randomly assigned to be fed since birth either a formula containing LCPUFA (arachidonic and docosahexaenoic acid) (+LCPUFA group) or the same formula without LCPUFA (-LCPUFA group). Associations of visfatin with anthropometric parameters, serum glucose, insulin, homeostasis model assessment index of insulin resistance, blood lipids, and adiponectin levels were examined. Serum visfatin levels were significantly higher in the +LCPUFA than in the -LCPUFA group (P < .001) and correlated positively with body weight z score (β = 0.31
Keywords: Adiponectin; Anthropometry; Blood Glucose; Body Weight; Cholesterol; Fatty Acids; Female; HDL; Humans; Infant; Infant Formula; Infant Nutritional Physiological Phenomena; Insulin; Insulin Resistance; Male; Metabolic Syndrome X; Newborn; Nicotinamide Phosphoribosyltransferase; Premature; Regression Analysis; Triglycerides; Unsaturated